تقييم مدى مساهمة التمكين الإداري في تحقيق الميزة التنافسية في المؤسسة الاقتصادية دراسة حالة مؤسسة اتصالات الجزائر بسكرة - مخلخل, زوينة; حاج يوسف, صارة (جامعة الوادي - University of Eloued, 2020)
The study aimed to know the role of administrative empowerment in achieving the competitive advantage of the Algerian Telecom in Biskra, where a questionnaire was used and distributed to (50) workers at the institution under study. In order to test the results of hypotheses. As the study found that the dimensions of administrative empowerment contribute to achieving a competitive advantage in a telecommunications organization Algeria Biskr
Evaluating the extent of the administrative empowerment contribution to achieving the competitive advantage in the economic establishment. A case study of Algeria Telecom in Biskr
مقال
Keywords: التمكين الإداري ; أبعاد التمكين الإداري ; الميزة التنافسية